+
f d =
f d
f d
X
1
f L ()
F  d <
Dene
f d =
u d + i
v d
X
+
u d
v d i
u d + i
v d.
(f + g)d =
f d +
g d.
X
f + g 
f  + 
g  < .
X
For (1), assume f, g real; the complex case follows from the real case.
Let h = f + g. Then h+ h = f + f + g + g , so h+ + f + g =
f + + g + + h . Since the integral is linear for nonnegative functions,
+
+
h + f + g = f + g + h
+
h h = f f + g g.
Thus, f + g = f + g.
For (2), let = a + bi for a, b R. Then
(a + bi)
(u + iv) = (a + bi)
u+i v
= a u + bi u + ai v b v.
+
(au) = (au) (au)
+
= a u a u
= a u a u = a u.
If a < 0, then
(au)
= (a) u (a) u+
= a u (a) u+
=a
u u
= a u.
au =
(au)
f d
f  d.
f d =
f d
ei .
Hence,
f d = ei
f d =
(ei f )d
X
X
X
i
= Re
e f d
X
=
Re(ei f )d
X
e f d =
f  d.
X
Dominated convergence.
and assume that f (x) = limn fn (x) (that is, the sequence fn con
verges pointwise). If there exists g L1 () such that fn (x) g(x)
for all n and for all x X, then f L1 () and
lim
fn f  d = 0, so lim
fn d =
f d.
n
=
2g d + lim inf
fn f  d
X
X
=
2g d lim sup
fn f  d.
X
Since
lim sup
fn f  d 0,
X
and so
fn f  d = 0.
lim
X
(fn f )d
fn f  d
X
X
fn d
f d
fn f  d 0
X
X
X
fn d
f d.
f d =
f d +
f d
E
E\N
EN
=
g d + 0 =
g d.
E\N
Completion of a algebra.
M = {E X  A, B M : A E B & (B \ A) = 0}.
Now dene (E) = (A) for all E M . Then M is a algebra and
this denition of is a measure.
The measure space (X, M , ) is a called the completion of the mea
sure space (X, M, ). A measure space is complete if it is equal to its
completion.
Note.
If f is only dened a.e. (say, except for aset N of measure
zero), then we can dene f (x) = 0 for all x N . f is well dened.
Theorem
(a) Let f : X [0, ] be measurable, E M, and
0.6.
f
d
=
0.
Then f = 0 a.e. on E.
E
1
(b) Let f L () and E f d = 0 for every E M. Then f = 0
a.e. on X.
Proof.
1
f d
f d
1/n d = (An ),
n
E
An
An
(A
)
=
0.
n
i=1
(b) Let
f
=
u
+
iv.
Choose
E
=
{
x

u
(
x
)
0
}
.
Then
f =
E
+
+
+
u + i E v E u = 0 and by (a), u = 0 a.e.
E
Theorem 0.7. Let Ek M such that k=1 (Ek ) < . Then almost
every x X lie in at most nitely many Ek .
Proof. Let
A = {x X  x Ek for innitely many k}. NTS (A) = 0.
Let g =
i=1 Ek .
Then x A g(x) = . We have
g d =
Ek d =
(Ek ) < .
X
i=1
1
i=1